T(1) = 1 T(n) = 1 + 2*T(n-1)Solution:
T(n) = 1 + 2*T(n-1) = 1 + 2*(1 + 2*T(n-2)) = 1 + 2 + 4*T(n-2) = 3 + 4*T(n-2) = 1 + 2 + 4*(1 + 2*T(n-3)) = 1 + 2 + 4 + 8*T(n-3) = 7 + 8*T(n-3) General form is 2k-1 + 2k*T(n-k). To use base case, let k = n-1 => 2n-1-1 + 2n-1*T(1). = 2*2n-1-1 = 2n-1. This is the guess.
T(1) = 1 T(n) = 4 + 3*T(n-1)Proof (by induction):
Base case (n=1): 31-2 = 1 = T(1) Inductive step: If T(k) = 3k-2 then T(k+1) = 3k+1-2 Proof: By the definition of T, T(k+1) = 4 + 3*T(k) By the inductive hypothesis, this is = 4 + 3*(3k-2) = 4 + 3k+1-6 = 3k+1-2.